EU labor market policy 2016: ideas, thought communities and policy change - Schellinger, Alexander (Basingstoke, 2016)
"The EU's 'social dimension' is a product of the ideology of the 1990s. Its employment field is directed to increase the employability of workers and the adaptability of labor market regimes. The book argues that this social-liberal approach is best explained with a set of ideas strategically advanced by 'thought communities' in the policy process."